2014
DOI: 10.1039/c4tc01607f
|View full text |Cite
|
Sign up to set email alerts
|

Growing gold nanoparticles on a flexible substrate to enable simple mechanical control of their plasmonic coupling

Abstract: A macroscopic mechanical strain can be used to control the coupling and therefore the electromagnetic field at the nanoscale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
109
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(113 citation statements)
references
References 33 publications
4
109
0
Order By: Relevance
“…Active tuning has been recently demonstrated where the plasmonic properties of a nanocomposite are continuously modified by mechanic deformation of the nanoparticle-matrix system in order to change the interparticle distance and hence select different spectral absorption regions. [11][12][13] Deformable nanocomposites have been reported to show plasmonic shifts up to around 70 nm for uniaxial deformations of about 20%.…”
Section: 2mentioning
confidence: 99%
See 2 more Smart Citations
“…Active tuning has been recently demonstrated where the plasmonic properties of a nanocomposite are continuously modified by mechanic deformation of the nanoparticle-matrix system in order to change the interparticle distance and hence select different spectral absorption regions. [11][12][13] Deformable nanocomposites have been reported to show plasmonic shifts up to around 70 nm for uniaxial deformations of about 20%.…”
Section: 2mentioning
confidence: 99%
“…15 The functionalization of elastomeric surfaces with noble metal nanoparticles has been proposed as an alternative to obtain stretchable plasmonic nanocomposites: this approach allows a very precise control of nanoparticle size and reciprocal distance; however, surface-functionalized elastomers are quite fragile and their stability has not yet been characterized. [11][12][13] In view of applications, a fundamental issue is the stability of the nanocomposite optical properties upon cyclic strain conditions; to date, no characterization of this aspect is reported in the literature, although there are clear evidences that nanoparticles in an elastomeric matrix are a dynamic system undergoing rearrangement and reorganization upon stretching. 19 Recently, we showed that neutral metal clusters produced in the gas phase and aerodynamically accelerated by a supersonic expansion can be implanted in a Polydimethylsiloxane (PDMS) substrate to obtain a nanocomposite with superior resilience and interesting optical properties for the fabrication of stretchable and conformable reflective gratings; 20,21 this approach is called Supersonic Cluster Beam Implantation (SCBI).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…17. Indeed, a single layer of citrate capped gold NPs (exhibiting a negative surface charge) are electrostatically bonded on a positively charged glass substrate by exploiting a dipping method.…”
mentioning
confidence: 99%
“…Since the frequency of the plasmonic resonance, and the resulting photo-induced heat, strongly depend on the NP size, shape, roughness, and dielectric function of the surrounding medium, 13,14 many related studies and investigations have been started, which include also the exploitation of optical, 15,38 magnetic, 16 and mechanical techniques. 17 In this letter, we utilize a particular class of soft materials, like Liquid Crystals (LCs), [18][19][20] to control the LSPR of NPs by exploiting a distinctive feature of LCs: the possibility of modifying their physical and optical properties by means of external stimuli. [21][22][23][24][25][26]39 In particular, we control and characterize the heat delivered by randomly distributed Gold NPs (GNPs) layered with Nematic Liquid Crystal (NLC) as an active medium.…”
mentioning
confidence: 99%